The Risk Genes SIRP5, CMC1, and ASAH1 as Potential Targets for the Diagnosis, Immunotherapy, and Treatment of Colon Adenocarcinoma by Single-Cell and Bulk RNA Sequencing Analysis - Xu, Zipeng; Gong, Jiantao; Hu, Weidong; Ge, Chen; Tong, Genxi; Cai, Fengjun; Zhu, Zhenghai; Yuan, Yihang; Chen, Chaobo (Current Medicinal Chemistry, 2024)
<span class=
Keywords: SIRP5